Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.24028/gzh.0203-3100.v42i5.2020.215085
|View full text |Cite
|
Sign up to set email alerts
|

About the influence of environmental conditions on the distribution of the SARS-CoV-19 virus in Ukraine

Abstract: Введение. Различные факторы окружающей среды (климатические, метеорологические, геомагнитные и др.) в определенной степени влияют на вспышки и распространение эпидемий и пандемий, послед-НАУЧНЫЕ СООБЩЕНИЯ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…For some oblasts, these parameters are as follows (in 10 3 cases): the Zaporizhzhia oblast is 227.2 and 6.1, the Mykolaiv oblast is 152.5 and 3.6, the Odesa oblast is 331.3 and 6.1, and the Kherson oblast is 110.0 and 2.9. It was confirmed that seasonal climatic variability and extreme weather conditions affected the spread of viruses [46,47].…”
Section: Dynamic Of the Health And Well-being Indicators Of The Regionmentioning
confidence: 73%
See 1 more Smart Citation
“…For some oblasts, these parameters are as follows (in 10 3 cases): the Zaporizhzhia oblast is 227.2 and 6.1, the Mykolaiv oblast is 152.5 and 3.6, the Odesa oblast is 331.3 and 6.1, and the Kherson oblast is 110.0 and 2.9. It was confirmed that seasonal climatic variability and extreme weather conditions affected the spread of viruses [46,47].…”
Section: Dynamic Of the Health And Well-being Indicators Of The Regionmentioning
confidence: 73%
“…The dynamics of changes of some health indicators can be clearly seen in Figures 8 and 9, but it is premature to state, unequivocally, that these changes are caused by climate impact drivers only. Further analysis is needed to determine the role of climate factors in changing health and well-being indicators, and, in particular, in the expansion of the SARS-CoV-2 pandemic [46,47].…”
Section: Discussionmentioning
confidence: 99%